The Effects of Blood Pressure Lowering on P-Wave Dispersion in Patients with Hypertensive Crisis in Emergency Setting - SAYAR, NURTEN (TAYLOR & FRANCIS INC, 2010)
Hypertensive emergency refers to a severe hypertension (HT) that is associated with new or progressive end-organ damage. In these clinical situations, blood pressure (BP) should be reduced immediately to prevent or minimize organ dysfunction. The present study evaluated the diagnostic value of two electrocardiographic indices in detecting patients, who are at risk for paroxysmal atrial fibrillation (PAF), in the setting hypertensive crisis. The study population consisted of 30 consecutive patients aged >= 40 years, who were admitted to the emergency room with hypertensive crisis. Electrocardiographic (ECG) recordings of the patients were performed before and after the treatment. The minimum (P-min) and maximum (P-max) P wave duration on ECG, and P-wave dispersion (P-d), which was defined as the difference between P-min and P-max, were measured. The mean P-d was 118.0 +/- 32.1 and 94.0 +/- 44.3 before and after the treatment, respectively. The decrease observed in the mean P-d was statistically significant (p = 0.005). The mean Pmax was 214.7 +/- 37.1 before the treatment, while it was 194.0 +/- 47.3 after the treatment, and the difference was significant (p = 0.021). The mean P-min was 96.7 +/- 26.3 and 100.0 +/- 41.0 before and after the treatment, respectively; however, the difference was not significant (p = 0.624). P-max and Pd display significant changes with acute treatment of HT. There is a need for larger prospective studies to clearly elucidate the diagnostic value of ECG indices, P-max and P-d as indicators of future PAF.
Keywords: P-wave duration; hypertensive crisis; P-wave dispersion; electrocardiographic index; ISOLATED SYSTOLIC HYPERTENSION; ATRIAL-FIBRILLATION; ELDERLY PROGRAM; RISK-FACTORS; STROKE; PREVALENCE; ABNORMALITY; MANAGEMENT; URGENCIES; ONSET